Study of the DNA Extraction from the Nail by Spin Column-based Nucleic Acid Purification - Kanchana Sujirachato; Piya Wongyanin; Pilaiwan Ramadjai; Alisa Ladsuk; Kingkan Pokkasap; Wisarn Worasuwannarak (Wolters Kluwer Medknow Publications, 2024)
Background: Nails are one of the objects that are more durable than other witness objects. This study was interested in whether the Spin column-based nucleic acid purification technique could extract DNA from nails to give satisfactory results. Aims and Objectives: This study aimed to evaluate the yield and quality of DNA extracted from the nail. MATERIALS AND METHODS: Nail samples from 15 males and 15 females over 18 were extracted using GeneAll® Exgene™ Cell SV Mini Kit. The DNA concentration and purity were measured using a NanoDrop Spectrophotometer, and the quality of DNA was assessed by polymerase chain reaction (PCR) using primers specific for human growth hormone (HGH). Results: The average yield of DNA was 0.816 μg (0.141-2.706 μg) obtained from the average nail weight of 30.2 mg (22.2-40.0 mg). The average DNA concentration was 27.2 ng/μL (4.7-90.2 ng/μL), corresponding to 30 μL in volume. Almost all DNA samples (96.7%) had high purity (A260/A280 ≥1.80) and gave a band of PCR product of the HGH gene on agarose gel electrophoresis. Conclusion: Spin column-based nucleic acid purification is recommended for nail DNA extraction due to its simplicity and high quality.